PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA MINIATUR TERHADAP HASIL BELAJAR IPAS PESERTA DIDIK KELAS V SD NEGERI KALUKU BODOA - Salsabilah, Mesyah; Muh. Erwinto Imran; Amri Amal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of the Problem-Based Learning (PBL) model assisted by miniature media on science and social (IPAS) learning outcomes of fifth-grade students at SD Negeri Kaluku Bodoa. This study used a quantitative approach with a quasi-experimental design in the form of a non-equivalent control group design. The sample consisted of 46 students divided into an experimental class and a control class. Data collection techniques included tests (pretest and posttest). The results showed that the application of the Problem-Based Learning model assisted by miniature media had a significant effect on students' learning outcomes. Students taught using this model showed better improvement compared to those taught using conventional methods. Thus, the use of Problem Based Learning assisted by miniature media can improve students' understanding, activeness, and learning outcomes in IPAS subjects.